Production of biochar from lignocellulosic biomass with acidic deep eutectic solvent and its application as efficient adsorbent for Cr (VI). (15th November 2021) - Zhang, Yali; Meng, Yahui; Ma, Li; Ji, Hairui; Lu, Xianqin; Pang, Zhiqiang; Dong, Cuihua
Abstract: Deep eutectic solvents (DES) as potential green solvents have gained tremendous attention in biorefinery. Herein, we presented a simple one-pot method for biochar production in acidic DES ( p -Toluenesulfonic acid monohydrate-choline chloride) at lower temperature (140 °C) using lignocellulose as feedstock. The results showed that the residual solid biomass treated in acidic DES were featured as biochar with excellent properties. The biochar exhibited the high content of carbon, plentiful oxygen-containing functional groups and porous structure, which endowed biochar with a superior adsorption capability on Cr (VI) up to 270.3 mg/g at 30 °C. The pseudo-second order model and Langmuir model can be used to perfectly describe the adsorption process, and adsorption behavior was assigned to chemical adsorption. In addition, the prepared biochar could be readily recycled via alkali-treated desorption. This study offered an environmental-friendly and cost-effective method for lignocellulose-derived biochar production. Graphical abstract: Image 1 Highlights: DES combined by choline chloride and p -toluenesulfonic acid possess high acidity. Biochar was produced with DES at mild conditions. The maximum adsorption capability to Cr (VI) reached 270.27 mg/g at 30 °C. The adsorption ability of biochar is significantly affected by the pH of Cr (VI) solution.